ENHANCED CREDIT BASED LOAD BALANCING IN CLOUD ENVIRONMENT - Singh, Jagdeep; Luthra, Mr. Pawan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Cloud computing is one of the latest and upcoming paradigm that offers huge benefits such as reduced time to market, unlimited computing power and flexible computing capabilities. It is a model that provides an on-demand network access to a shared pool of computing resources It comprises a large number of concepts primarily Load Balancing, Scheduling, etc. This paper discusses load balancing as a mechanism to distribute the workload evenly to all nodes in the system to achieve a higher resource utilization and user satisfaction. It helps in allocation and de-allocation of instances of applications withoutÂ  Â failure. This paper reports a new load balancing technique using modified credit based system using task length, task priority and its cost. The proposed algorithm has been implemented in cloudsim toolkit and its comparison with existing algorithm has been discussed in the paper.